Restoration of tryptophan hydroxylase functions and serotonin content in the Atlantic croaker hypothalamus by antioxidant treatment during hypoxic stress - Rahman, Md. Saydur; Thomas, Peter (Frontiers in Neuroscience, 2014)
Antioxidants are prototypical scavengers of oxygen-free radicals and have been shown to prevent neuroendocrine dysfunction in vertebrates during oxidative stress. In the present study, we investigated whether antioxidant treatment can reverse hypoxia-induced down-regulation of hypothalamic tryptophan hydroxylase (TPH) and serotonergic functions in Atlantic croaker. Hypothalamic neuronal contents of TPH-1 and TPH-2 proteins, serotonin (5-hydroxytryptamine, 5-HT) and its precursor, 5-hydroxytryptophan (5-HTP) as well as hypothalamic TPH-1 and TPH-2 mRNA expression and TPH activity were measured in croaker after exposure to hypoxia and treatment with pharmacological agents. Multiple injections of N-ethylmaleimide, a sulfhydryl alkylating agent, caused comparable decreases in hypothalamic TPHs functions and 5-HT contents to that induced by hypoxia exposure (dissolved oxygen: 1.7 mg/L for 4 weeks) which were partially restored by repeated injections with a nitric oxide synthase (NOS)-inhibitor and/or vitamin E. Double-labeled immunohistochemical results showed that TPHs and 5-HT neurons were co-expressed with neuronal NOS (nNOS, a neuroenzyme) that catalyzes the production of nitric oxide, a free radical, in hypothalamic neurons. These results suggest that hypoxia-induced impairment of TPH and serotonergic functions are mediated by nNOS and involve the generation of free radicals and a decrease in the antioxidant status. This study provides, to our knowledge, the first evidence of a protective role for an antioxidant in maintaining neural TPHs functions and 5-HT regulation in an aquatic vertebrate during hypoxic stress.